The relationship between smoking status and smoking cessation practice for health workers in Surabaya - Kurnia D. Artanti; Santi Martini; Mahmudah Mahmudah; Sri Widati; Diva Adila; Muhammad A. Rahman (Journal of Public Health in Africa, 2023)
Background: Indonesia is one of the countries that have a high smoker prevalence globally. Therefore, a smoking cessation program is key to reducing the smoking prevalence in Indonesia. The role of health workers is necessary for smoking cessation programs. However, smoking behavior among health workers could limit smoking cessation practices for patients.